Highly elastomeric poly(3-hydroxyoctanoate) based natural polymer composite for enhanced keratinocyte regeneration. Issue 7 (3rd May 2017) - Rai, Ranjana; Roether, Judith A.; Knowles, Jonathan C.; Mordan, Nicola; Salih, Vehid; Locke, Ian C.; Gordge, Michael P.; McCormick, Aine; Mohn, Dirk; Stark, Wendelin J.; Keshavarz, Tajalli; Boccaccini, Aldo R.; et al.
ABSTRACT: A novel nanocomposite material combining the biocompatible, elastomeric, natural, biodegradable homopolymer poly(3-hydroxyoctanoate) (P(3HO)) with hemostatic and antibacterial bioactive glass nanoparticles (n-BG) was developed as a matrix for skin related applications. P(3HO) is a unique member of the family of natural polyhydroxyalkanoate biopolymers. The P(3HO)/n-BG composite films were fabricated using the solvent casting method. Microstructural studies revealed n-BG particles both embedded in the matrix and deposited on the surface, which introduced nanotopography and increased its hydrophilicity. The composite exhibited an increase in the Young's modulus when compared to the control, yet maintained flexible elastomeric properties. These changes in the surface topography and chemistry of the composite system led to an increase of protein adsorption and cytocompatibility for the seeded human keratinocyte cell line. The results from this study demonstrated that the fabricated P(3HO)/n-BG composite system is a promising novel matrix material with potential applications in skin tissue engineering and wound healing. GRAPHICAL ABSTRACT: